The economic evaluation of Cystic echinococcosis control strategies focused on zoonotic hosts: A scoping review. - Jo Widdicombe; María-Gloria Basáñez; Mahbod Entezami; Daniel Jackson; Edmundo Larrieu; Joaquín M Prada (PLoS Neglected Tropical Diseases)
Background Cystic echinococcosis (CE) is a zoonotic neglected tropical disease (zNTD) which imposes considerable financial burden to endemic countries. The 2021-2030 World Health Organization's roadmap on NTDs has proposed that intensified control be achieved in hyperendemic areas of 17 countries by 2030. Successful interventions for disease control, and the scale-up of programmes applying such interventions, rely on understanding the associated costs and relative return for investment. We conducted a scoping review of existing peer-reviewed literature on economic evaluations of CE control strategies focused on Echinococcus granulosus zoonotic hosts. Methodology/principal findings Database searches of Scopus, PubMed, Web of Science, CABI Direct and JSTOR were conducted and comprehensively reviewed in March 2022, using predefined search criteria with no date, field or language restrictions. A total of 100 papers were initially identified and assessed for eligibility against strict inclusion and exclusion criteria, following the Preferred Reporting Items for Systematic reviews and Meta-Analyses extension for Scoping Reviews (PRISMA-ScR) guidelines. Bibliography review of included manuscripts was used to identify additional literature. Full review of the final manuscript selection (n = 9) was performed and cost data for control interventions were extracted. Conclusions/significance There are very little published data pertaining to the cost and cost effectiveness of CE control interventions targeting its zoonotic hosts. Data given for costs are often incomplete, thus we were unable to perform an economic analysis and cost effectiveness study, highlighting a pressing need for this information. There is much scope for future work in this area. More detailed information and disaggregated costings need to be collected and made available. This would increase the accuracy of any cost-effective analyses to be performed and allow for a greater understanding of the opportunity cost of healthcare decisions and resource allocation by stakeholders and policy makers for effective and cost-effective CE control.